Investigation on Load Characteristics of Hinged Connector for a Large Floating Structure Model under Wave Actions - Song, Xuemin; Liu, Weiqin; Wu, Hao (Journal of marine science and engineering, 2023)
The super-large floating bodies are often designed as multimodule structures linked by connectors, and the load and strength evaluation of the connector structure becomes an essential work in the design procedure of these floating bodies. In this paper, the hydrodynamic experimental model of a double floating body with a hinged connecter is designed first, and a hinged connector is adopted for connecting the double module floating bodies. A test is conducted for load calibration. Then, the experiments are carried out in the towing tank under different wave conditions. The load characteristics of the hinged connector are measured in the experiment. The numerical simulations for the load of the hinged connector are conducted based on the commercial platform ANSYS. The time history of the vertical, lateral and longitudinal loads for the hinged connector are illustrated. Finally, the comparison and analysis between the experimental results and numerical results is presented, and the conclusions are drawn, which indicate that the numerical method is effective to predict the load characteristics of a hinged connector. Above all, the methods and conclusions of this study are used to provide reference and guidance for the structural design of hinged connectors for floating bodies.